Low voltage ride through (LVRT) enhancement of a two-stage grid-connected photovoltaic system based on finite-control-set model predictive control strategy - Gholipour, Ali; Farhadi-Kangarlu, Mohammad; Neyshabouri, Yousef; Talavat, Vahid (Center of Biomass & Renewable Energy (CBIORE), 2025)
Grid-connected photovoltaic (PV) systems face numerous challenges during grid faults, including fault detection, synchronization, over-current protection, fluctuations in DC-link voltage, and compliance with active and reactive power requirements. This paper presents a control strategy based on finite-control set model predictive control (FCS-MPC) to enhance the LVRT capability of these systems. The strategy incorporates a battery energy storage system (BESS) to improve overall performance. Unlike traditional approaches, the proposed method integrates the control of all switches in boost converters, the BSS controller, and the neutral point clamped (NPC) inverter in one controller. It also combines the Maximum Power Point Tracking (MPPT) within a unified multi-objective cost function framework. By utilizing the positive sequence component of the current, this strategy facilitates symmetrical sinusoidal current injection during grid faults, effectively regulates the DC-link voltage, and maintains balanced capacitor voltages in the NPC inverter while avoiding over-current conditions. The BSS plays a key role in energy management by allowing the PV system to continue operating in MPPT mode during grid faults and enabling the storage of excess solar energy during disturbances. This capability ensures compliance with LVRT grid codes by efficiently managing the injection of reactive and active currents into a compromised grid. The proposed method reduces reliance on traditional cascaded hierarchical control loops, enhancing both dynamic response and system robustness during disturbances. The simulation studies carried out in MATLAB/Simulink environment on a 100 kW three-phase grid-connected PV system demonstrate the effectiveness of the proposed approach. The results indicate that the strategy maintains PV system performance at the maximum power point while significantly improving LVRT capability and overall grid stability. According to the simulation results, although in severe grid faults, the negative sequence grid current is kept at less than 1% and the voltage balance of the capacitors in the NPC inverter is maintained accurately. Also, the voltage ripples on the DC-link capacitors are limited to 7% in the fault period. In conclusion, this integrated control strategy effectively addresses the challenges posed by grid faults and enhances the operational efficiency of grid-connected PV systems, thereby contributing to the resilience of renewable energy infrastructures.